Perancangan Thermal Pyshical Distance Pendeteksi Suhu Tubuh Otomatis di Kantor Layanan Masyarakat Kota Padang - Isra Mouludi; Musdirwan Musdirwan; Candrianto Candrianto; Miratul Hasni; Firdaus Jamsan; Edo Rantou Wijaya; Wahyuni Amalia (Politeknik ATI Padang, 2022)
According to World Health Organization, one of the symptoms of someone infected with the corona virus is fever. Body temperature at the time of fever for adults is above 37 °C. Anticipation has been done by using a gun thermal scanner, which is expensive, not to mention how to use this tool, which requires direct physical contact when scanning. Recently, WHO has released a prevention protocol with the concept of physical distancing, which means that a safe distance between humans must be maintained at least 1.5 meters to prevent transmission. The current government program requires every agency to follow the health protocol during the transition period by implementing the New Normal. Correspondence activities at the Community Service Office such as the lurah or sub-district office have begun to be active again in serving the needs of the community, so this office will become a gathering place for many people, so that public services can be provided and also maintain the health of employees from physical contact with the people being served. must always apply the new normal health protocol to the public and serving officers so as not to contract the Covid-19 virus. The solution offered is to make a